Parasitic contamination in green vegetables from open markets in Gampaha District, Sri Lanka: Implications for human health - Nayana Gunathilaka; Rashmi Kavindya; Kithsiri Gunawardena; Deepika Amerasinghe (PLoS ONE, 2025)
Intestinal parasitic infections in Sri Lanka have received little attention due to their perceived low prevalence. Consuming raw vegetables without proper washing is one of the main ways to transmit intestinal parasitic infections. Therefore, this study investigated the contamination of parasites in vegetables. A cross-sectional study was conducted from August 2023 to January 2024 at fifty selected open markets in ten cities (Ragama, Miriswatta, Kirillawala, Kadawatha, Balummahara, Kiribathgoda, Peliyagoda, Weliweriya, Imbulgoda and Gampaha) in Gampaha District, Sri Lanka. Four vegetable types, namely Centella asiatica (Gatu kola) [n = 162], Ipomoea aquatica (Kankun) [n = 150], Alternanthera sessilis (Mukunuwenna) [n = 160] and Lactuca sativa (Lettuce) [n = 148] that are consumed either raw or half cooked were selected. Approximately 50 g of each vegetable was taken randomly at each sampling attempt. Each sample was dipped in the Tween 20 (5%) in a shaker for 15 minutes, followed by sedimentation overnight and centrifugation (2000 × g for 15 min). Both supernatant and sediment were examined under a light microscope to detect parasitic stages. The overall prevalence of parasitic contamination in the samples was 21.29% (n = 132). Centella asiatica indicated the highest contamination (37.65% [61/162]). Lactuca sativa had the lowest contamination (2.02% [3/148]). Parasites including protozoan (Entamoeba histolytica, Giardia lamblia, Toxoplasma gondii, Blastocystis hominis, Paramphistomum spp and Balantidium coli) and helminths (Ascaris spp., Hymenolepis spp., Strongyloides stercoralis, Trichuris spp, Taenia spp, Toxocara canis and hookworms) were detected. Blastocystis hominis was the most predominant (4.68%; n = 29). Toxocara sp, G. lamblia and Eimeria sp were identified as least abundant (0.77%; n = 5). Every sample contained at least one parasitic contamination. A significant difference between the type of vegetables and the existence of parasites was identified (P = 0.008). The parasitic stages identified could cause infections among people with poor food hygienic/ preparation practices. Therefore, health authorities must educate consumers on precautionary measures to prevent re-emerging intestinal parasitic infections in Sri Lanka.